The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1590/s0036-36342005000200007
|View full text |Cite
|
Sign up to set email alerts
|

Violencia de género: actitud y conocimiento del personal de salud de Nicaragua

Abstract: The health care personnel generally were observed to have high values in regard to an attitude of rejection towards GBV. However, we found barriers that show persisting traditional beliefs, such as considering violence to be a personal issue. Therefore, in order, to ensure a substantial improvement, better training about this subject is needed in medical school curricula with an emphasis on the gender perspective. The finding of the present study will allow improvements in health care reforms at the first leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
9

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 12 publications
0
16
0
9
Order By: Relevance
“…24 Tal preferência pode significar receio do profissional em abordar a questão da violência com as mulheres. Pesquisa com médicos e enfermeiros da Nicarágua mostrou que a paciente é inquirida sobre violência somente quando há suspeita de que esta esteja ocorrendo.…”
Section: Discussionunclassified
“…24 Tal preferência pode significar receio do profissional em abordar a questão da violência com as mulheres. Pesquisa com médicos e enfermeiros da Nicarágua mostrou que a paciente é inquirida sobre violência somente quando há suspeita de que esta esteja ocorrendo.…”
Section: Discussionunclassified
“…This attitude is closely related to conceptions of the private status of violence and it is not appropriate to be explored in the healthcare setting (19) . A study (7) identified that health professionals do not question women when suspecting violence for several reasons, such as lack of time and resources, lack of preparation, fear of causing embarrassment and frustration, because they feel impotent to solve the situation.…”
Section: When They Come With Wounds [] We Have To Ask Because It Imentioning
confidence: 99%
“…Além disso, tais estudos apontam barreiras pessoais dos profissionais como fator que desfavorece a implementação de ações adequadas para enfrentar a violência doméstica nos serviços de saúde. Destacam-se, entre elas, o sentimento de impotência frente à situação, bem como o receio da reação do agressor diante de alguma intervenção (Rodríguez-Bolaños, Márquez-Serrano & Kageyama-Escobar, 2005;Kiss, 2004;De Ferrante, Santos & Vieira, 2009). Isso corrobora também com, um estudo encontrado sobre crenças dos profissionais de saúde, realizado em município da mesma região da presente pesquisa, no qual foi apontado que em relação às providências tomadas diante da suspeita ou confirmação do ato violento, os agentes comunitários de saúde admitiram não tomar nenhuma nos casos de violência doméstica, apresentando como principais entraves a falta de apoio e o acompanhamento dos órgãos jurídicos e o medo denunciar, justificado pelo possível comprometimento na comunidade onde vivem e trabalham .…”
Section: Discussionunclassified